Enemies - Chmakova, Svetlana, 1979- (Chmakova, Svetlana, 1979- Berrybrook Middle School., 2022)
Felicity is an artist and a gamer with big dreams, but her sister Letty makes fun of her because she never finishes anything. Inspired by the TV show, "Piranha Pit," Felicity decides to join the Entrepreneur Club and compete in a contest to prove to Letty that she can finish something. In the club, she finds herself competing against Joseph, who she used to be friends with in elementary school until they drifted apart in middle school. She doesn't really understand why they stopped being friends, and soon she starts to wonder if they are enemies. Things get even more complicated when tensions rise between Felicity and her friend Tess after they can't decide on an idea for their business proposal, and Felicity has to deal with a member of her Spanish group who won't do their share of the work. She must try to find a way to smooth things over with her various friend groups before she loses everything.